BORDER DEVELOPMENT POLICY: PERU-ECUADOR AND ITS RELATIONSHIP WITH THE NATIONAL DEFENSE - Ochoa Garcia, Roxi Fiorella (2021)
This research was carried out with the purpose ofknow what is the level of correlation between the policyPeru-Ecuador border development and defensenational. The quantitative approach, developed duringthe period 2018-2019, had a non-experimental design, ofcorrelational descriptive scope, cross-sectional,considering a total population made up of143 officials from the Ministry of Foreign Affairsand the Ministry of Defense, with a total samplemade up of 102 subjects. For the collection processof data, a questionnaire was applied, whose measurementcorresponded to a Likert-type scale. It was concluded thatexisting border policies have a relationshipdirectly with national defense.